MENUMBUHKAN KARAKTER CINTA BUDAYA SISWA SD MELALUI VIDEO GAMES MARBEL BUDAYA NUSANTARA - Eka Nindes Rezki Burki; Fitriana Anggraini; Maysiska Ruci; Arita Marini (Bajang Institute, 2023)
The character of love for culture is a character that must be grown in children as early as possible. The elementary school level is the right time to cultivate the character of loving culture through character education in learning. By understanding the character of love for culture, it will make a person protect the culture of his own people with awareness from within himself. However, in reality, in order to foster the character of love for culture, elementary school students experience various challenges. One of them is the character of elementary school students who prefer to play rather than study. Because of these problems, this research has the goal of examining the effectiveness of cultivating the character of love for culture in elementary school students through Marbel Budaya Nusantara video games. By introducing the archipelago's cultural heritage, it can be used as a means to foster the character of loving culture. A sense of love for culture will grow along with seeing the diversity of the archipelago's cultural heritage. By applying learning while playing, it is hoped that elementary school students will more easily accept this character education.